Endophytic Fungi Piriformospora indica Mediated Protection of Host from Arsenic Toxicity - Mohd, Shayan; Shukla, Jagriti; Kushwaha, Aparna S.; Mandrah, Kapil; Shankar, Jai; Arjaria, Nidhi; Saxena, Prem N.; Narayan, Ram; Roy, Somendu K.; Kumar, Manoj (Frontiers in Microbiology, 2017)
Complex intercellular interaction is a common theme in plant-pathogen/ symbiont relationship. Cellular physiology of both the partners is affected by abiotic stress. However, little is known about the degree of protection each offers to the other from different types of environmental stress. Our current study focused on the changes in response to toxic arsenic in the presence of an endophytic fungus Piriformospora indica that colonizes the paddy roots. The primary impact of arsenic was observed in the form of hyper-colonization of fungus in the host root and resulted in the recovery of its overall biomass, root damage and chlorophyll due to arsenic toxicity. Further, fungal colonization leads to balance the redox status of the cell by adjusting the antioxidative enzyme system which in turn protects photosynthetic machinery of the plant from arsenic stress. We observed that fungus has ability to immobilize soluble arsenic and interestingly, it was also observed that fungal colonization restricts most of arsenic in the colonized root while a small fraction of it translocated to shoot of colonized plants. Our study suggests that P. indica protects the paddy (Oryza sativa) from arsenic toxicity by three different mechanisms viz. reducing the availability of free arsenic in the plant environment, bio-transformation of the toxic arsenic salts into the insoluble particulate matter and modulating the antioxidative system of the host cell.